The Study of Project on Community Development Participation t at Mueang District Nakhon Ratchasima Province - Putburee, Jakkrid; Sawaengdi, Bhawat; Pensuk, Jinkamol; Ngamchaiyaphum, Prakrong; Kimsua, Chonlawat (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Nakhon Ratchasima Buddhist College is involved in the community development project in Mueang Nakhon Ratchasima District. A budget has been set aside for the academic service project of Nakhon Ratchasima College of Science, Mahamakut Buddhist University. The project will run from May 1, 2023, to October 31, 2023. The initiative in Mueang District, Nakhon Ratchasima Province, aims to foster community development. The initiative aims to serve as a hub for the pursuit of academic knowledge in Buddhism and to offer Buddhist academic services to the community at large. Thus, the study's objectives were to: 1) investigate how the public and students in Mueang district, Nakhon Ratchasima province, participate in community development; 2) conduct research at Nakhon Ratchasima Buddhist College for the academic year 2023. 2) Examine respondents' attitudes regarding students' and individuals' involvement in community development. 3) Describe the relationship between the variables affecting students' and individuals' involvement in community development. Methodology: Sixty students from the Nakhon Ratchasima Buddhist College, which is situated in the Mueang area of the province, made up the sample for this quantitative study. The mean, standard deviation, and percentages were the study's instruments. Results: (1) The level of student and public participation in Nakhon Ratchasima Buddhist College-sponsored community development projects was significantly high; (2) the level of student and public participation in community development projects has encouraged people in societies was significantly high at the.05 level; and (3) there was a positive statistical correlation, at the.01 level, between critical success factors and people's participation in community development. Conclusion: The research on a community development project in the province of Nakhon Ratchasima's Mueang District. The research team discovered that the project's participants were deeply committed to advancing community development in the province of Nakhon Ratchasima's Mueang District. Teachers, staff members, and students who offered academic services and expressed satisfaction with the initiative comprised the study's sample. Regarding the individuals involved in the project, they reported greater creativity and public spirit, which made them pleased.